2008
DOI: 10.1021/jp801607m
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Structural Disorder on the Photoluminescence Emission of PZT Powders

Abstract: Intense and broad visible photoluminescent (PL) band was observed at room temperature in disordered Pb(Zr 0,53 Ti 0,47 )O 3 powders. Structural order-disorder was evaluated by different methods. XANES results pointed to the presence of different coordination modes of disordered Ti powders, and in the ordered sample the local structure around titanium atoms is characteristic of the structurally ordered PZT with only TiO 6 units. Only samples containing simultaneous structural order and disorder in their network… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
1
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 24 publications
1
9
1
1
Order By: Relevance
“…Nevertheless, the bands at 2.56 and 3.35 eV show a shift in the maximum peak position which depending if the phase is rhombohedral or tetragonal will shift to 2.61 and 3.45 eV, respectively. Note that in the PZT polycrystalline samples without Nb, the three well resolved emission bands were also shown, in contrast with other reports (Longo et al, 2008;Chang et al, 2001) where the emission for polycrystalline PZT is very low and broad or absent. For these materials (PZTN) the emission is bigger in 1 or 2 order than PLZT.…”
Section: Substitution In B Sitecontrasting
confidence: 88%
See 1 more Smart Citation
“…Nevertheless, the bands at 2.56 and 3.35 eV show a shift in the maximum peak position which depending if the phase is rhombohedral or tetragonal will shift to 2.61 and 3.45 eV, respectively. Note that in the PZT polycrystalline samples without Nb, the three well resolved emission bands were also shown, in contrast with other reports (Longo et al, 2008;Chang et al, 2001) where the emission for polycrystalline PZT is very low and broad or absent. For these materials (PZTN) the emission is bigger in 1 or 2 order than PLZT.…”
Section: Substitution In B Sitecontrasting
confidence: 88%
“…The PL at 2.56 eV, which shows the highest intensity in all PZTN compositions and is associated to a transition between a shallow defect in the band gap and the valence band, see Figure 8. These levels are associated to oxygen vacancies, with simple or double ionization which is in accordance with the classification of Longo et al, (2008), vacancies bonded to clusters of TiO 5 in disordered regions. In principle, the incorporation of Nb 5+ in PZT samples would be producing more lead vacancies than oxygen vacancies.…”
Section: Substitution In B Sitesupporting
confidence: 77%
“…[1][2][3][4] Among the various ferroelectric materials, PbZr 1-x Ti x O 3 (PZT) thin films are widely investigated due to their stability in most of the device operating ranges and remarkable ferroelectric properties. The superior properties of PZT thin films are ascribed to their extraordinary dielectric and piezoelectric behaviors around the morphotropic phase boundary (MPB, about Zr:Ti=52:48) where the properties are enhanced.…”
Section: Introductionmentioning
confidence: 99%
“…A broad visible PL band, with a large Stokes shift, has been also related to the recombination of selftrapped excitons (STE) [27]. Structural order-disorder in several ceramics prepared by the solid-state reaction method [20], and by polymeric precursor method [28][29][30][31], has been used to explain the room temperature PL spectra observed in these amorphized materials. Such studies have shown that the broad PL emission band, covering a large part of the visible spectra of the structurally disordered compounds, is very similar to that observed for nano-crystalline PL emission [27,30].…”
Section: Optical Propertiesmentioning
confidence: 99%